Inspiration from Old Dyes: Tris(stilbene) Compounds as Potent Gram‐Positive Antibacterial Agents. Issue 52 (18th November 2013) - Boulos, Ramiz A.; Man, Nikki Y. T.; Lengkeek, Nigel A.; Hammer, Katherine A.; Foster, Niki F.; Stemberger, Natalie A.; Skelton, Brian W.; Wong, Pan Yu; Martinac, Boris; Riley, Thomas V.; McKinley, Allan J.; Stewart, Scott G.
Abstract Herein we describe the preparation and structure‐activity relationship studies on range of stilbene based compounds and their antibacterial activity. Two related compounds, each bearing carboxylic acid moieties, exhibit good activity against several bacterial strains, including methicillin‐resistant Staphylococcus aureus MRSA (ATCC 33592 and NCTC 10442). Compound 10 was most active against Moraxella catarrhalis with minimum inhibitory concentrations (MICs) of 0.12–0.25 μg mL−1 and against Staphylococcus spp. with MICs ranging from 2–4 μg mL−1. The derivative 17 showed increased activity with MICs of 0.06–0.25 μg mL−1 against M. catarrhalis and 0.12–1 against Staphylococcus spp. This level of activity is similar to that reported for S. aureus for antibiotics, such as vancomycin, with MICs of ≤2.0 μg mL−1 and clindamycin with MICs of ≤0.5 μg mL−1. As an indicator of toxicity, 17 was tested for its ability to lyse sheep erythrocytes, and showed low haemolytic activity. Such results highlight the value of tris(stilbene) compounds as antibacterial agents providing suitable properties for further development.